2013
DOI: 10.1155/2013/689235
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cellulolytic Bacterial Cultures Grown in Different Substrates

Abstract: Nine aerobic cellulolytic bacterial cultures were obtained from the Leibniz Institute DSMZ-German Collection of Microorganisms and Cell Culture (DSMZ) and the American Type Culture Collection (ATCC). The objectives of this study were to characterize the cellulolytic bacteria and to determine the optimum moisture ratio required for solid state fermentation (SSF) of palm kernel cake (PKC). The bacteria cultures were grown on reconstituted nutrient broth, incubated at 30°C and agitated at 200 rpm. Carboxymethyl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
6
18
0
Order By: Relevance
“…In comparison, the most active β-glucosidase activity responsible for reducing sugar liberation from cellobiose was exhibited between Day 4 and Day 6 of SSF. This finding was in agreement with Alshelmani et al [55,93], who reported that high CMCase, xylanase, and mannanase activity was exhibited by P. polymyxa , Bacillus megaterium, and Bacillus amyloliquefaciens during Day 4 of SSF of PKC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In comparison, the most active β-glucosidase activity responsible for reducing sugar liberation from cellobiose was exhibited between Day 4 and Day 6 of SSF. This finding was in agreement with Alshelmani et al [55,93], who reported that high CMCase, xylanase, and mannanase activity was exhibited by P. polymyxa , Bacillus megaterium, and Bacillus amyloliquefaciens during Day 4 of SSF of PKC.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, LAB are generally known as “generally recognized as safe” (GRAS) and “quantified presumption of safety” (QPS) due to their beneficial probiotic characteristics [50,51]. The postbiotic metabolites produced by Lactobacillus plantarum strains, one of the major and important species of LAB that employed in this study, have been extensively reported as a versatile health supplement for rat and livestock as a growth promoter to produce safer and healthier meat for consumers [52,53,54,55]. Paenibacillus polymyxa and other LAB, such as Lactobacillus salivarius, could reduce the crude fiber and improved nutrient digestibility of broiler fed with fermented lignocellulosic biomass [56,57,58,59].…”
Section: Introductionmentioning
confidence: 99%
“…(2016) Bacillus subtilis ST-141, Saccharomycetes N5Protease, lipase, amylase, xylanaseStainless steel fermentation tank48 h at 30 °CWang et al. (2017)Palm kernel cake Aspergillus wentii Lipase, amylase, dextranase, cellulase, pectinase, β-glucosidase, mannanase, xylanase48 h at 30 °CMuangkeow and Chinajariyawong (2009) Aspergillus wentii Lipase, amylase, dextranase, cellulase, pectinase, β-glucosidase, mannanase, xylanase48 h at 30 °CMuangkeow and Chinajariyawong (2013)Cellulolytic bacteriaCellulase, xylanase, mannanaseFlask4 to 7 d at 30 °CAlshelmani et al. (2013)Cellulolytic and hemicellulolytic bacteriaCellulase, xylanase, mannanaseFlask12 dAlshelmani et al.…”
Section: Solid-state Fermentationmentioning
confidence: 99%
“…Palm kernel cake has been used as an energy source for ruminants and non-ruminants because of its palatability and crude protein content of about 14.5% to 19.24% (Sundu et al., 2006, Ezieshi and Olomu, 2007). The limitation of using palm kernel cake in feeding monogastric animal, especially poultry is due to poor amino acid balance, high indigestible fibre, coarse texture, grittiness, possible deterioration under unhygienic conditions and high concentrations of NSP such as mannan, xylan and cellulose (Alimon, 2004, Sundu et al., 2006, Alshelmani et al., 2013, Alshelmani et al., 2014). The indigestible portions are actually NSP comprising 78% β-mannan, 12% cellulose, 3% arabinoxylans and 3% water-insoluble glucoxylans (Sundu et al., 2006).…”
Section: Effect Of Solid-state Fermentation On the Nutrient Compositimentioning
confidence: 99%
“…T [33][34][35] was obtained from the Bacillus Genetic Stock Center (Columbus, OH). In these assays, P. polymyxa 25A2…”
Section: Cellulolytic Activitymentioning
confidence: 99%